2016
DOI: 10.1080/14737159.2016.1174578
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-derived exosomes in acute myeloid leukemia for detection of minimal residual disease: are we ready?

Abstract: The recent emergence of plasma-derived exosomes as biomarkers of leukemic relapse has introduced the potential for more sensitive non-invasive monitoring of leukemia patients based on the molecular and genetic analysis of the exosome cargo. In principle, the protein, lipid, miRNA, mRNA or DNA profiles of exosomes in patients’ plasma that associate with leukemic relapse can be identified. The diagnostic/prognostic value of these profiles could then be validated in prospective clinical studies. Here, we consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 39 publications
(55 reference statements)
0
31
0
Order By: Relevance
“…In particular, T-EVs have the potential to be the most informative predictors in non-invasive tumour monitoring [119,120]. For example, Taylor et al found and verified eight miRNAs of EVs that could identify and differentiate stages of tumours, and potentially be diagnostic/prognostic biomarkers of ovarian cancer [121].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…In particular, T-EVs have the potential to be the most informative predictors in non-invasive tumour monitoring [119,120]. For example, Taylor et al found and verified eight miRNAs of EVs that could identify and differentiate stages of tumours, and potentially be diagnostic/prognostic biomarkers of ovarian cancer [121].…”
Section: Discussion and Outlookmentioning
confidence: 99%
“…The first clinical trial using NK92 cell reported initial signs of antitumor activity, 52 and this was followed by other clinical studies reporting that unmodified NK‐92 cells can be safely infused into patients with advanced treatment‐resistant malignancies to show encouraging antitumor responses in patients with lung cancer 53 . A recent phase I clinical trial in AML investigated the safety of activated NK‐92 (aNK) cells and reported no grade 3 to 4 toxicities related to cell infusion and some signs of clinical activity, with two out of seven patients showing stable disease and one patient showing a reduction in blast percentage from 70% to 48% 54 . In another recent phase I study, irradiated NK‐92 cells were used to treat 12 lymphoma or MM patients, and the cell infusions were also well tolerated, with 2 patients achieving complete response, 2 showing minor responses, and 1 reporting clinical improvement 55 .…”
Section: Nk Cellsmentioning
confidence: 99%
“…Moreover, utilizing exosomes can be a helpful strategy to eliminate minimal residual diseases (MRDs). 107 It seems that cell origin makes difference in uptake efficiency of exosomes between target cells. Accordingly, NK cells uptake the myeloid system-derived exosomes such as K562 and Jurkat ALL cell line with a higher rate when compared to exosomes derived from another cell lines such as HepG2 (human liver cancer cell line) and MCF-7 (breast cancer cell line) cell line.…”
Section: Exosomes Effect On Leukemia Treatmentmentioning
confidence: 99%